Depth‐Resolved Enhanced Spectral‐Domain OCT Imaging of Live Mammalian Embryos Using Gold Nanoparticles as Contrast Agent. Issue 35 (15th July 2019) - Huang, Yali; Li, Minghui; Huang, Doudou; Qiu, Qi; Lin, Wenzhen; Liu, Jiyan; Yang, Wensheng; Yao, Youliang; Yan, Guoliang; Qu, Ning; Tuchin, Valery V.; Fan, Shanhui; et al.
Abstract: High‐resolution and real‐time visualization of the morphological changes during embryonic development are critical for studying congenital anomalies. Optical coherence tomography (OCT) has been used to investigate the process of embryogenesis. However, the structural visibility of the embryo is decreased with the depth due to signal roll‐off and high light scattering. To overcome these obstacles, in this study, combined is a spectral‐domain OCT (SD‐OCT) with gold nanorods (GNRs) for 2D/3D imaging of live mouse embryos. Inductively coupled plasma mass spectrometry is used to confirm that GNRs can be effectively delivered to the embryos during ex vivo culture. OCT signal, image contrast, and penetration depth are all enhanced on the embryos with GNRs. These results show that after GNR treatment, more accurate spatial localization and better contrasting of the borders among organs can be observed on E9.5 and E10.5 mouse embryos. Furthermore, the strong optical absorbance of GNRs results in much clearer 3D images of the embryos, which can be used for calculating the heart areas and volumes of E9.5 and E10.5 embryos. These findings provide a promising strategy for monitoring organ development and detecting congenital structural abnormalities in mice. Abstract : An optical coherence tomography (OCT) system is combined with gold nanorods (GNRs) for 2D/3D imaging of live mouse embryos. GNRs are delivered to the embryos during ex vivo culture. OCT signal, image contrast, and penetration depth are all enhanced on the embryos with GNRs. Moreover, a much clearer 3D embryo image can be used to calculate the volume of its heart.